Application of Interactive and Intelligent Packaging for Fresh Fish Shelf-Life Monitoring - Ibrahim, Saber; Fahmy, Hager; Salah, Shimaa (Frontiers in Nutrition, 2021)
Smart packaging, also known as intelligent packaging, which is responsive to external stimuli as well as moisture, light, oxygen, heat, pH and bacterial growth, has found extensive applications in food safety, bacterial response, and medical packaging. Interactive packaging has a great integration scientific bases in add information to food products. This work deals with combining frontline food sciences, smart and interactive packaging will be applied for future production in nutrition packaging to verify the best degree of food safety and population demands as third generation of packaging technology. High qualified duplex laminated package with nano-encapsulated pH monitoring label for fresh fish was printed. In addition, interactive qr-code icon was combined in designed package with important information about cooking, smart packaging, and fish quality. Particle size, zeta potential and surface area were measured for nano-encapsulated indicator which exhibited 74.4 nm, 23.6 mV and 88.9 m2/g, respectively. Overall migration, water vapor & oxygen permeability and printing properties of 11 color spot were evaluated by x-rite before and after cold storage period with no detectable change in the rate of color change (∆E). with excellent results as suitable and safe package. Bacterial count in packaged food is a key factor in assessing the quality and safety of food. The microbial infection of the tested sample was examined by the counting of the microbial colonies in the agar plate media (CFU agar plate method). There is nice agreement between microbial count and smart indicator color change as effective tool for sustainable food quality and safety.